DYNAMIC BEHAVIOR STUDY OF BLOCK FOUNDATION AND GROUP PILE USING FONDAMEN AND PLAXIS 2D SOFTWARE AT PLTP ULUBELU AND PLTMG DURI PROJECT - MAULANA HAKIM (NIM : 15009038 ), ABI
Dynamic foundation is a foundation that specially designed to withstand dynamic loads that work on the foundation. The need of dynamic foundation design is correlated with some variables. Development of knowledge and technology related to structural modeling has advanced in the late years. One of the example of the development are software that can model and calculate dynamic behavior of soil. Plaxis 2D is a software that has been developed and has an ability to perform dynamic analysis using finite element method. The other software, Fondamen, is a software that specially created to calculate dynamic foundation using lump mass method. PLTP Ulubelu and PLTMG Duri projects are two projects that have dynamic loads worked on their foundation design. Shallow foundation is used at PLTP Ulubelu project and pile group is used at PLTMG Duri. Based on the cases, dynamic study for those two foundations at both project area is performed using Plaxis 2D and Fondamen. It can be summarized from the study result that Plaxis 2D and Fondamen gave the biggest result that has a little differences. But in the same time it has been found that both software gave a big different to the response due to vertical dynamic loads.